Profile of judicialization in access to antineoplastic drugs and their costs: a cross-sectional, descriptive study based on a set of all lawsuits filed between 2016 and 2018 in a state in the Northeast Region of Brazil - Fábio Henrique Cavalcanti de Oliveira; José Eudes de Lorena Sobrinho; Antônio da Cruz Gouveia Mendes; Haynne Magalhães Santos Gutman; Geraldo Jorge Filho; Ulisses Ramos Montarroyos (BMC, 2022)
Abstract Background The judicialization of the acquisition of medication for healthcare is not restricted to Brazil but can also be found in other Latin American countries, despite the existence of a universal health system in the case of Brazil, the Unified Health System (known as the SUS). Right-to-medicines litigation has existed ever since the emergence of a high demand for treatment of Acquired Immuno-deficiency Syndrome (AIDS) but the current focus is on cancer. Pharmaceutical Assistance (PA) is the area within the SUS that is responsible for ensuring access to medication and the aim of this article is thus to draw up a profile of litigation related to PA in one economically significant state in the Northeast Region of Brazil, in terms of the following characteristics of lawsuits: the plaintiff filing the lawsuit; medical and health information; the cost of acquiring the requested medications; and the proportion accounted for by spending on antineoplastic drugs. Methods A cross-sectional, descriptive study was conducted of lawsuits filed between 2016 and 2018 at the Litigation Center of the State of Pernambuco Department of Health. Results A total of 2,947 lawsuits containing at least one requested medication were analyzed. The majority of the plaintiffs were male (51.7%); 49.8% of the requests originated in the Unified Health System (SUS), and plaintiffs were primarily patients in the Metropolitan region of the State capital, Recife. The most frequent cancers involved were those classified by the ICD as C61, C71 and C50. The median general expense on medications for the actions was U$1,734.94. Considering antineoplastic drugs alone, the cost exceeded U$7,500 per lawsuit over the three years, given that the median unit price for antineoplastic drugs is approximately US$65 compared to US$4 for non-antineoplastic drugs. Conclusion The present study is of relevance to the field of public health and examines how a profile of such healthcare litigation can be used as a tool for managing and improving decision-making in times of economic austerity.